Using Scientific Activities to improve the Learning Behavior of Disabled Students in Ramkhamhaeng University. - Chatwirakom, Wanida (European Journal of Sustainable Development, 2016)
This is an experimental research project aiming to study and develop the use of scientific activities as teaching and learning tools to improve hearing impaired students’ learning behavior. The research population consisted of handicapped students with inaudibility. The sample population was a group of 14 hearing-impaired students who enrolled at Ramkhamhaeng University’s Hua Mak Campus in Bangkok, Thailand. These were students who willingly participated in making scientific picture frames. The data and details were gathered through the use of a checklist to evaluate scientific skills involving scientific picture frames. Then the participating students were interviewed and a thorough observation was made on their learning behaviors when they were engaged in the aforementioned scientific activities. The data collected was then analyzed using a computer software program to present descriptive statistics and arithmetic mean. The findings are as follows: 1. In general, the students engaged in these scientific activities displayed a good level of performance. Seven of them excellently carried out their tasks while there was only one student whose performance was below the standard. 2. Overall, their learning behaviors exhibited were satisfactory. Four students displayed distinctive learning behaviors and three of them displayed unsatisfactory learning behaviors. Keywords, Scientific Activities , Improve the Learning Behavior of Disabled Students ???????